Exploitation of an ancestral pheromone biosynthetic pathway contributes to diversification in Heliconius butterflies. Issue 1979 (27th July 2022) - Cama, Bruna; Ehlers, Stephanie; Szczerbowski, Daiane; Thomas-Oates, Jane; Jiggins, Chris D.; Schulz, Stefan; McMillan, W. Owen; Dasmahapatra, Kanchon K.
Abstract : During courtship, male butterflies of many species produce androconial secretions containing male sex pheromones (MSPs) that communicate species identity and affect female choice. MSPs are thus likely candidates as reproductive barriers, yet their role in speciation remains poorly studied. Although Heliconius butterflies are a model system in speciation, their MSPs have not been investigated from a macroevolutionary perspective. We use GC/MS to characterize male androconial secretions in 33 of the 69 species in the Heliconiini tribe. We found these blends to be species-specific, consistent with a role in reproductive isolation. We detected a burst in blend diversification rate at the most speciose genus, Heliconius ; a consequence of Heliconius and Eueides species using a fatty acid (FA) metabolic pathway to unlock more complex blends than basal Heliconiini species, whose secretions are dominated by plant-like metabolites. A comparison of 10 sister species pairs demonstrates a striking positive correlation between blend dissimilarity and range overlap, consistent with character displacement or reinforcement in sympatry. These results demonstrate for the first time that MSP diversification can promote reproductive isolation across this group of butterflies, showcasing how implementation of an ancestral trait, the co-option of the FA metabolic pathway for pheromone production, can facilitate rapid speciation.